Effect of parachute delivery on red blood cell (RBC) and plasma quality measures of blood for transfusion. Issue Volume 61:Issue S1 (2021)Supplement (16th July 2021) - Bates, Mark; Watts, Sarah; Doughty, Heidi; Woolley, Tom; Miles, Andrew; Barry, Liam; Jenner, Dominic; Sedman, Andrew; Purcell, Robert; Kirkman, Emrys
Abstract: Background: Parachute airdrop offers a rapid transfusion supply option for humanitarian aid and military support. However, its impact on longer‐term RBC survival is undocumented. This study aimed to determine post‐drop quality of RBCs in concentrates (RCC), and both RBCs and plasma in whole blood (WB) during subsequent storage. Study design and methods: Twenty‐two units of leucodepleted RCC in saline, adenine, glucose, mannitol (SAGM) and 22 units of nonclinical issue WB were randomly allocated for air transportation, parachute drop, and subsequent storage (parachute), or simply storage under identical conventional conditions (4 ± 2°C) (control). All blood products were 6–8 days post‐donation. Parachute units were packed into Credo Cubes, (Series 4, 16 L) inside a PeliCase (Peli 0350) and rigged as parachute delivery packs. Packs underwent a 4‐h tactical flight (C130 aircraft), then parachuted from 250 to 400 ft before ground recovery. The units were sampled aseptically before and after airdrop at weekly intervals. A range of assays quantified the RBC storage lesion and coagulation parameters. Results: Blood units were maintained at 2–6°C and recovered intact after recorded ground impacts of 341–1038 m s −2 . All units showed a classical RBC storage lesion and increased RBC microparticles during 42 days of storage. Fibrinogen and clotting factors decreased in WB during storage. Nevertheless, no significant difference was observed between Control and Parachute groups. Air transportation and parachute delivery onto land did not adversely affect, or shorten, the shelf life of fresh RBCs or WB. Discussion: Appropriately packaged aerial delivery by parachute can be successfully used for blood supply.